Harnessing tethered nitreniums for diastereoselective amino-sulfonoxylation of alkenes - Shyam Sathyamoorthi; Appasaheb K. Nirpal; Dnyaneshwar A. Gorve; Steven P. Kelley (Beilstein Journal of Organic Chemistry)
We present the first examples of alkene amino-sulfonoxylation reactions that leverage the unique reactivity of carbamate tethered N-alkoxy nitrenium ions. In almost all cases examined, the reactions deliver product with exquisite regioselectivity and diastereoselectivity. The protocols followed are operationally very simple and only use commercial I(III) reagents and sulfonic acids, amounting to a metal-free protocol for alkene amino-oxygenation. No special precautions need be taken to exclude air or ambient moisture, and the products are amenable to further transformations.